Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Section 6.6 - Solving Quadratic Equations by Factoring - Exercise Set: 64

Answer

The solutions are -3 and 0 and 3.

Work Step by Step

3$x^{3}$-27x=0 3x($x^{2}$-9)=0 3x(x-3)(x+3)=0 x=0 or x-3=0 or x+3=0 x=0 or x=3 or x=-3 The solutions are -3 and 0 and 3. Check Let x=-3 3$x^{3}$-27x=0 3$(-3)^{3}$-27(-3)=0 3(-27)-27(-3)=0 -81+81=0 0=0 Let x=3 3$x^{3}$-27x=0 3$(3)^{3}$-27(3)=0 3(27)-27(3)=0 81-81=0 0=0 Let x=0 3$x^{3}$-27x=0 3$(0)^{3}$-27(0)=0 3(0)-0=0 0-0=0 0=0
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.